Immunoassay and mass cytometry revealed immunological profiles induced by inactivated BBIBP COVID‐19 vaccine. Issue 11 (19th July 2022) - Cheng, Zhangkai J.; Huang, Huimin; Liu, Qiwen; Zhong, Ruifen; Liang, Zhiman; Xue, Mingshan; Liu, Mingtao; Li, Siping; Wang, Hongman; Zheng, Peiyan; Zheng, Chunfu; Sun, Baoqing
Abstract: With the global prevalence of COVID‐19 and the constant emergence of viral variants, boosters for COVID‐19 vaccines to enhance antibody titers in human bodies will become an inevitable trend. However, there is a lack of data on antibody levels and the protective effects of booster injections. This study monitored and analyzed the antibody potency and the antibody responses induced by the booster injection in the subjects who received three vaccine doses. The study was conducted in a multicenter collaboration and recruited 360 healthy adults aged 20–74. Participants received the first, second, and booster doses of inactivated Sinopharm/BBIBP COVID‐19 vaccine at 0, 1, and 7 months. Vaccine‐induced virus‐specific antibody levels (SARS‐COV‐2‐IgA/IgM/IgG) were monitored at multiple time points, surrogate virus neutralization test (sVNT), and the spatial distribution and proportion of immune cells and markers were analyzed using the CyTOF method before vaccination and a month after the second dose. The titers of SARS‐CoV‐2‐IgA/IgM/IgG and neutralizing antibodies increased to a high level in the first month after receiving the second dose of vaccine and declined slowly after that. The antibody levels of SARS‐CoV‐2‐IgG and sVNT were significantly increased at 0.5 months after the induction of the booster ( p  < 0.05). Despite a downward trend, the antibody levels were still high in the following 6 months. The B cell concentration (in humoral sample) a month after the second injection was significantly reduced compared to that before the vaccine injection ( p  < 0.05). The proportion of the C01 cell cluster was significantly decreased compared with that before vaccine injection ( p  < 0.05). Individual cell surface markers showed distinctions in spatial distribution but were not significantly different. This study has shown that serum antibody titer levels will decrease with time by monitoring and analyzing the antibody efficacy and the antibody reaction caused by the booster injection of healthy people who received the whole vaccination (completed three injections). Still, the significant peak of the antibody titer levels after booster highlights the recall immune response. It can maintain a high concentration of antibody levels for a long time, which signifies that the protection ability has been enhanced following the injection of booster immunization. Additionally, CyTOF data shows the active production of antibodies and the change in the immunity environment.